IoT-Based Real-Time Train Position Monitoring System Using GPS - Andriana, Andriana; Setia, Hipni; Ramdani, Dani; Zulkarnain, Zulkarnain; Rahman, Sutisna Abdul; Adiprabowo, Tjahjo (Internet of Things and Artificial Intelligence Journal, 2025)
In this modern era, the need for fast, efficient, and quality transportation is important, one of which is in the railway sector. Although trains have special tracks, accidents can still occur due to various factors, such as infrastructure damage and officer negligence. One of the accidents that occurred on January 5, 2024, between the Turangga train and the Bandung Commuter Line caused fatalities and injuries. To overcome this problem, a real-time train position monitoring system is needed. This research aims to design and develop a train position monitoring system using a GPS module. GPS (Global Positioning System) is widely used for tracking systems. This system monitors the position of trains and other information that can be accessed by station officers and the general public. By using the ESP32 microcontroller and NEO-6M GPS module, this system is expected to improve the safety of train travel, minimize the potential for accidents, and provide more accurate information about train arrival times at the station. This research also aims to test the performance of the monitoring system in real conditions. It is hoped that with this system, train accidents due to negligence can be minimized, and provide significant benefits for officers and the public who use train transportation.